Vegetal oil-based ketogenic diet improves inflammation and fibrosis in experimental metabolic dysfunction-associated steatohepatitis - Provera, Alessia; Ramavath, Naresh Naik; Gadipudi, Laila Lavanya; Vecchio, Cristina; Caputo, Marina; Antonioli, Alessandro; Tini, Sabrina; Sheferaw, Anteneh Nigussie; Reano, Simone; Filigheddu, Nicoletta; Manfredi, Marcello; Barberis, Elettra; et al. (Frontiers in Immunology, 2025)
Background and aimsMetabolic dysfunction-associated steatohepatitis (MASH) represents a growing cause of liver cirrhosis and hepatocellular carcinoma (HCC). However, effective therapy for MASH is still lacking. Despite recent studies suggest that ketosis might improve MASH evolution, the mechanisms involved have not been explored since common ketogenic diets cause severe steatohepatitis in mice. In this study, we have investigated the capacity of a new-formulated ketogenic diet (KD) containing vegetal fat in improving liver alterations associated with experimental MASH.MethodsMASH was induced in C57BL/6 mice by feeding a cholesterol-enriched Western Diet (WD) for up to 16 weeks, followed by switching animals to KD for an additional eight weeks.ResultsWe observed that KD administration greatly increased ketone body production and significantly reduced liver and body weights. Moreover, liver proteomic analysis and functional tests evidenced an improved glucose and lipid metabolism along with insulin resistance in KD-fed mice. These metabolic effects were associated with an amelioration in MASH-associated gut dysbiosis and with an improvement of hepatic steatosis, parenchymal injury and liver fibrosis. From the mechanistic point of view mice receiving KD showed a significant reduction in liver TREM2-positive monocyte-derived macrophages forming crown-like aggregates along with a lowering in the hepatic expression of pro-inflammatory/pro-fibrogenic markers such as CCL2, IL-12, CD11b, α1-procollagen, TGF-β1, osteopontin, and galectin-3. Consistently, in vitro experiments showed that β-hydroxybutyrate supplementation reduced TREM2 and galectin-3 expression by cultured Raw 264.7 macrophages.ConclusionsAltogether, these results indicate that ketogenic diet based on vegetal fat effectively improves MASH metabolic derangements and steatohepatitis, and it might represent a potential therapeutic strategy in this disease.